Les évolutions du travail enseignant en France et en Europe : facteurs de changement, incidences et résistances dans l’enseignement secondaire - Maroy, Christian (Revue française de pédagogie. Recherches en éducation, 2006)
Confronted with a school system and a society rapidly changing, this article presents a summary of what we know about the actual evolution of the work of high school teachers. The work teachers are asked to do tends to be the same all over Europe: Besides the traditional tasks of preparing lesson plans, teaching and assessing, teachers are required to take part in the life of their schools, be involved in collective projects, get training, etcetera. Concerning the effective work done, writings about education acknowledge that the teacher’s job is getting more intense and complicated. It is getting more intense not only because of longer workdays but also because of an increase in the tasks required and the complexity of classroom work. However, this trend can not be explained only by the changing of the students attending school today but, in British and American schools, by school policies based on assessment and accountability. To conclude, we will ask ourselves why teachers react so coldly, even with some resistance, to school reforms that are supposed to help them. Is the problem only a problem of resisting changes, linked to obsolete professional practices? To us the teachers’ discontent seems to be far deeper and due to their withdrawing from or resisting to reforms, whenever those reforms highlight the deprofessionalizing of teachers.
Keywords: Europe; conditions de travail de l’enseignant; développement de l’enseignement; enseignement secondaire; professionnalisation